2016
DOI: 10.1200/jop.2016.013516
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging a Team Mental Model to Develop a Cancer Anorexia-Cachexia Syndrome Team

Abstract: This article discusses the care of a 62-year-old man with non-small-cell lung cancer and associated cancer anorexia-cachexia syndrome (CACS), and demonstrates common challenges faced by such patients and their family caregivers. The case description illustrates the fragmented approach of various disciplines to the patient's CACS care, resulting in undertreatment, delayed and burdensome visits, and patient and caregiver frustration and emotional distress. The mounting problems that arise for the patient over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…This review found 19 publications[ 16 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 ] reporting a multimodal intervention for cancer cachexia with a psychosocial component and published from January 2013 to March 2021. They included complex interventions used in practice ( n = 3),[ 27 28 38 ] tested in the context of a feasibility study ( n = 6)[ 16 24 29 32 36 40 ] or pilot/early phase trial ( n = 5),[ 23 24 31 33 39 ] and theorized approaches drawing on existing literature and expert opinion ( n = 6). [ 25 26 30 34 35 37 ] The interventions tested were found to be feasible and safe (when adverse events and safety issues were reported [ n = 8]).…”
Section: Resultsmentioning
confidence: 99%
“…This review found 19 publications[ 16 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 ] reporting a multimodal intervention for cancer cachexia with a psychosocial component and published from January 2013 to March 2021. They included complex interventions used in practice ( n = 3),[ 27 28 38 ] tested in the context of a feasibility study ( n = 6)[ 16 24 29 32 36 40 ] or pilot/early phase trial ( n = 5),[ 23 24 31 33 39 ] and theorized approaches drawing on existing literature and expert opinion ( n = 6). [ 25 26 30 34 35 37 ] The interventions tested were found to be feasible and safe (when adverse events and safety issues were reported [ n = 8]).…”
Section: Resultsmentioning
confidence: 99%
“…3,25 Frameworks, such as the team mental model, have been found to optimise team processes and functioning. 54 Multidisciplinary cancer prehabilitation and rehabilitation programs providing individualised care demonstrate capacity to improve nutritional status, muscle mass and strength, fatigue and performance status. [55][56][57][58] These interventions require the specialist skills of various MDT members as part of a coordinated approach to individualised treatment of cancer-related malnutrition and sarcopenia and can be accessed through acute hospital services, community-based services or general practices.…”
Section: Namentioning
confidence: 99%
“…Alongside medical nutrition therapy, interventions that have been shown to contribute to optimising nutritional status and body composition include exercise, management of treatment side effects through optimising medications and the management of anorexia and dysphagia 3,25 . Frameworks, such as the team mental model, have been found to optimise team processes and functioning 54 . Multidisciplinary cancer prehabilitation and rehabilitation programs providing individualised care demonstrate capacity to improve nutritional status, muscle mass and strength, fatigue and performance status 55‐58 .…”
Section: Recommendationsmentioning
confidence: 99%
“…[ 22 ] Cancer cachexia is a complex syndrome and the goal of the treatment is to fix the various broken pieces using an interdisciplinary team approach. [ 6 23 ]…”
Section: Cancer Cachexiamentioning
confidence: 99%
“…[ 1 ] Team approaches and holistic care to the management of cancer cachexia have been proposed as a model of improving patient care and outcomes. [ 6 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%